The Analysis and Critique of the French Phonetics - Mohamad-Hossein Otroshi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the field of phonetics of French as a foreign language, studies have been conducted in recent decades, among which French Phonetics can be considered as the first book for Iranian students in undergraduate and postgraduate of French as a foreign language. In this paper, using a methodological analysis, based on the position and the role of phonetic ability in the communicative-actional approaches and the methods of phonetics in the teaching of foreign languages, we tried to evaluate the French Phonetics with respect to the goals and needs of French language teaching. The results showed that the book’s educational approach is a combination of articulatory and descriptive phonetics which only focuses on phonetic foreign language teaching (Parisian French pronunciation), regardless of the diversity of Iranian students’ first language. Considering the scientific developments in the field of foreign language teaching, linguistics, and in particular phonetics (such as verbo-tonal method and acoustic phonetics based on the use of technology), this textbook, even in the eighth edition, has failed to keep pace with the current trends in the field and could not fulfill the needs of French language teaching and learning in the context of Iran.